2023
DOI: 10.1002/jcad.12464
|View full text |Cite
|
Sign up to set email alerts
|

School counselors’ perceived school climate, leadership practice, psychological empowerment, and multicultural competence before and during COVID‐19

Abstract: Following a population‐based randomized design, we investigated changes of school counselors’ psychological empowerment, multicultural competence, and leadership practice, as well as their perception of school climate from before to during COVID‐19. Specifically, school counselors were randomized into two conditions: (a) the pre‐COVID‐19 condition (n = 506) and (b) the current‐COVID‐19 condition (n = 542). Participants in the pre‐COVID condition responded to survey items following a retrospective manner based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…This is especially troublesome because school counselors have a shared responsibility in facilitating the socioemotional and behavioral development of all students (ASCA, 2019), yet large caseloads may prevent them from supporting students most in need. Taken collectively, with the increased mental health needs among all students, these reports offer preliminary evidence suggesting that inadequate student-to-school-counselor ratios may contribute to schools’ inability to efficaciously respond to the mental health and well-being needs of students during the pandemic (Hilts & Liu, 2023). Beyond the need for further investigation regarding the relationship between school counselor caseloads and student demographics, more insights concerning potential inequities in caseload sizes and school counselor demographics may be useful.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially troublesome because school counselors have a shared responsibility in facilitating the socioemotional and behavioral development of all students (ASCA, 2019), yet large caseloads may prevent them from supporting students most in need. Taken collectively, with the increased mental health needs among all students, these reports offer preliminary evidence suggesting that inadequate student-to-school-counselor ratios may contribute to schools’ inability to efficaciously respond to the mental health and well-being needs of students during the pandemic (Hilts & Liu, 2023). Beyond the need for further investigation regarding the relationship between school counselor caseloads and student demographics, more insights concerning potential inequities in caseload sizes and school counselor demographics may be useful.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Fairchild and Zins (1986) found that school counselors with larger caseloads (750+ students) were actually more likely to be involved in accountability efforts than those with smaller caseloads. Based on these limited and discrepant findings, scholars’ call for further examination of the relationship between caseload sizes and actual practices, such as the leadership practices of school counselors, is not surprising (Hilts & Liu, 2023; Scarborough & Culbreth, 2008).…”
Section: Introductionmentioning
confidence: 99%